Back to Nature With Fenceless Farms—Technology Opportunities to Reconnect People and Food - Swain, David L.; Charters, Stuart M. (Frontiers in Sustainable Food Systems, 2021)
The development and application of the fence was one of the earliest forms of agricultural technology in action. Managing the supply of animal protein required hunter gatherer communities to be able to domesticate and contain wild animals. Over the ages the fence has become ingrained in the very fabric of society and created a culture of control and ownership. Feudal landlords provided ‘peasants’ with access to the ‘commons’ to ensure they were able to feed themselves. But the rise of commerce and textile manufacturing, on the back of wool, was underpinned by the fence which controlled livestock movement and human access. Garett Hardin’s article titled ‘The Tragedy of the Commons’ suggested that shared land, typified by access to a fenceless common resource, was doomed to failure due to a human instinct for mistrust and exploitation. Perhaps the fence has created an ingrained societal cultural response. While natural ecosystems do have physical boundaries, these are based on natural environmental zones. Landscapes are more porous and resilience is built up through animal’s being able to respond to dynamic changes. This paper explores the opportunity for remote monitoring technologies to create open fenceless landscapes and how this might be integrated into the growing need for humans to access animal protein.